The chilean experience deterring illicit corporate equity management - Pardow Lorenzo, Diego (Derecho Público Iberoamericano, 2012)
This paper analyzes the investigations on potential misconducts conduc ted by the Chilean public enforcer SVS between 1990 and 2012. The evidence reveals two groups of problems: on the one hand, the SVS has leaved a substantial region of the market unmonitored; on the other hand, the level of specific deterrence is generally low and relies greatly on indirect mechanisms of punishment. Such results suggest that future reforms should facilitate private enforcement on both the extensive and the intensive margin. Whereas improving the performance of the SVS on the extensive margin should mitigate its monitoring bias, the improvements on the intensive margin are meant to increase the punishment experienced by offenders.